Authorship Identification of Punjabi Poetry - Pandian, A.; Wahid, Stephen; Tokas, Yash; V.Ramalingam, V. (International Journal of Engineering and Technology, 2018)
The problem of identifying the author of an anonymous text is basically Authorship Identification. It is nothing but a single-label text-categorization task, from the ML point-of-view. An assumption is made that an unknown text’s author can be differentiated by comparing a few lexical features extracted from theunknown text with the same of texts having known authors. In this paper, the process of Authorship Identification is executed on Punjabi poetry dataset consisting of Punjabi poems written by 5 different poets. Various features broadly categorised as statistical (word-count, char-count, etc.), syntactical (i.e. lexical) and semantically (language dependent) are first selected using the J48 Decision Tree Algorithm. The selected features are in turn, used as an input to multiple classifiers (like SVM, SMO, Bayes Net & Naive Bayes) and the proposed system’s validation is evaluated on the basis of Precision, Recall, F-score and Accuracy.